LA NOVELA TERRÍGENA DE MARIO VERDUGO: UN ENCUADRE MAULA DEL CAMPO CHILENO. - Ceresa, Constanza (Revista Chilena de Literatura, 2022)
La novela terrígena (2011) by Chilean poet Mario Verdugo, depicts a trickster image of the province through a “maula framing”, which shows both the flaw and the potential of the static representation of Chilean territory in Criollista literature. Through a novel that does not narrate, Verdugo’s conceptual poetry deploys an impersonal gaze that selects and combines symbolic and material remains of the countryside of the Maule area to construct a terrígena imaginary (Mariano Latorre) stripped of national symbols and deformed by referents of the sci-fi world and mass culture. This new way of imagining the province and in particular, the rural area becomes a performative exercise that reflects on the possibilities of literature to represent these territories against the identity discourses that have tended to overcode them, and in turn make visible the evident temporal and spatial dislocation produced by the capitalist machinery in its global process, in which the human figure is increasingly blurred as a point of reference.